Association of Magnet Status With Hospitalization Outcomes for Ischemic Stroke Patients. Issue 4 (April 2017) - Bekelis, Kimon; Missios, Symeon; MacKenzie, Todd A.
Abstract : Background: It is not clear whether Magnet recognition by the American Nurses Credentialing Center (nursing excellence program) is associated with improved patient outcomes. We investigated whether hospitalization in a Magnet hospital is associated with improved outcomes for patients with ischemic stroke. Methods and Results: We performed a cohort study of patients with ischemic stroke from 2009 to 2013, who were registered in the New York Statewide Planning and Research Cooperative System database. Propensity‐score‐adjusted multivariable regression models were used to adjust for known confounders, with mixed effects methods to control for clustering at the facility level. An instrumental variable analysis was used to control for unmeasured confounding and simulate the effect of a randomized trial. During the study period, 176 557 patients were admitted for ischemic stroke, and met the inclusion criteria. Of these, 32 092 (18.2%) were hospitalized in Magnet hospitals, and 144 465 (81.8%) in non‐Magnet institutions. Instrumental variable analysis demonstrated that hospitalization in Magnet hospitals was associated with lower case‐fatality (adjusted difference, −23.9%; 95% CI, −29.0% to −18.7%), length of stay (adjusted difference, −0.4; 95% CI, −0.8 to −0.1), and rate of discharge to a facility (adjusted difference, −16.5%; 95% CI, −20.0% to −13.0%) in comparison to non‐Magnet hospitals. The same associations were present in propensity‐score‐adjusted mixed effects models. Conclusions: Using a comprehensive all‐payer cohort of patients with ischemic stroke in New York State, we identified an association of treatment in Magnet hospitals with lower case‐fatality, discharge to a facility, and length of stay. Further research into the factors contributing to the superiority of Magnet hospitals in stroke care is warranted.